Tympanometry and computed tomography measurement of middle ear volumes in patients with unilateral chronic otitis media - Shukla, Anuj Kumar; Kanaujia, S. K.; Kaushik, Sandeep; Saxena, Nishant Saurabh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Tympanometry and computed tomography (CT) measurement of middle ear volume in patients with unilateral chronic otitis media. Methods: The prospective study was conducted on 50 patients of diagnosed unilateral chronic otitis media showing clinical symptoms which affect quality of life. Patients who were fulfilling inclusion criteria after screening were selected for study. We studied patients who had a unilateral tympanic membrane (TM) perforation and a normal TM in the contralateral ear which act as control group to estimate the ME volume in the lesioned ear. Further we have compared pre and postoperative middle ear volume (measured by CT and tympanometry) in control & diseased ear to correlate middle ear volume results obtained by CT and Tympanometry. Results: The mean value of MEV measured by tympanometry and CT were (1.343±0.580) and (1.106±0.380) respectively (Figure 1). Volume measurement by tympanometry is higher as compared to volume measured by CT in lesioned ear, hence tympanometry measured volume in diseased ear were higher that measured by CT which is closer to normal values in both normal and Diseased ears. Also hearing shows improvement in diseased ear after surgery due to restoration of middle ear volume closer to normal. Conclusions: It was concluded in our study that CT is more reliable investigation for middle ear volume measurement as compared to Tympanometry in diseased as well as normal ears.